Novel Generalisation of Some Fixed Point Results Using a New Type of Simulation Function - Mohd Hasan (Transactions on Fuzzy Sets and Systems)
I am utilizing a brand-new simulation function that has previously been developed by eminent mathematicians and that uses fuzzy metric-like spaces to establish new fixed point theorems. Here, this is demonstrated that the current conclusion is unquestionably a unified one that can generalize earlier current results. To further demonstrate the relevance of my findings, a few additional theorems and corollaries are demonstrated. Additionally, several excellent examples are provided to show how useful my findings are. I provide an application of my major finding in the conclusion.